Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan Hotel Holiday Inn Kemayoran, Jakarta - Khaisya Nur Haliza; Heribertus Jani (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of leadership style and organizational culture on employee performance at Holiday Inn Kemayoran Jakarta. This study uses a field research method with a quantitative approach. This research was conducted with the employee analysis unit of Hotel Holiday Inn Kemayoran Jakarta, with a sample of 50 people. The sampling method used is non-probability sampling with saturation sampling technique obtained by 50 respondents, the data collection technique is a questionnaire. The data processing method uses validity test, reliability test, classical assumption test, and hypothesis test using spss version 26. tcount 0,916 < ttable 2,01174. Organizational culture has an effect on employee performance partially with the results of the t test, namely the significance value of 0.000 <0.05 and the tcount value of 5.437 > ttable 2.01174. Leadership style and organizational culture affect employee performance simultaneously with the results of the f test, namely the significance value of 0.000 <0.05 and the Fcount 37.562> Ftable 3.19.